Pengaruh Perceived Social Presence, Perceived Ease Of Use, Perceived Usefulness, Dan Attitude Towards Online Shopping Terhadap Niat Beli Pada Jakarta Notebook.Com - Sianadewi, Jessica Hani; Widyarini, Lydia Ari; Wibowo, Wahyudi (Kajian Ilmiah Mahasiswa Manajemen, 2017)
E-commerce in Indonesia is growing rapidly at this time. Process online purchases affected by many factors. One of them is technology factor, as explained in TAM (Technology Acceptance Model) theory, which is ease of use factor and benefit. This research is purpose to find out and analyze the influence of perceived social presence, perceived ease of use, perceived usefulness, and attitude towards online shopping to purchase intention on jakartanotebook.com. Sample that it takes in this research amount 150 respondents who has been visit and use searching feature on jakartanotebook.com site. Data was collected using questionnaire and processed using Structural Equation Model (SEM) technic. The result of this research showed that perceived social presence has a positive influence on perceived usefulness, perceived ease of use has a positive influence on perceived usefulness, perceived ease of use has a positive influence on attitude towards online shopping, and attitude towards online shopping has a positive influence on purchase intention on jakarta notebook.com